Tinea Unguium Yang Disebabkan Microsporum sp. : Sebuah Kasus Jarang - Saviestya, Kaorie Bunga; Widasmara, Dhelya (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Onychomycosis is a fungal infection of the nails that can be caused by dermatophytes, non-dermatophytes, and yeast, while tinea unguium is an infection of the nails caused by the dermatophyte group. Onychomycosis is known to occur in 2-18.5% of the population worldwide where it is 4-20 times more common in toenails than fingernails. In patients with systemic lupus erythematosus, it was reported that 25% experienced nail changes where the most common abnormality was onycholysis. The following is a report of a 27-year-old female patient with complaints of damaged and brittle left toe nails accompanied by itching. From the dermatological examination of the left I-V digiti pedis, discoloration and onychodystrophy were found. Examination of 20% KOH on nail clippings shows long-branched hyphae. The results of the fungal culture showed the growth of Microsporum sp. This case report discusses a rare case of tinea unguium caused by Microsporum sp.